2020
DOI: 10.1016/j.xcrm.2020.100128
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Kinase Index: A Method to Prioritize Understudied Kinases as Drug Targets for the Treatment of Cancer

Abstract: Summary The approval of the first kinase inhibitor, Gleevec, ushered in a paradigm shift for oncological treatment—the use of genomic data for targeted, efficacious therapies. Since then, over 48 additional small-molecule kinase inhibitors have been approved, solidifying the case for kinases as a highly druggable and attractive target class. Despite the role deregulated kinase activity plays in cancer, only 8% of the kinome has been effectively “drugged.” Moreover, 24% of the 634 human kinases are u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 91 publications
2
70
0
Order By: Relevance
“…Survival analysis also showed overexpression of PKMYT1 leads to lower overall survival in ACC, BLCA, KICH, KIRC, KIRP, LGG, and LUAD cancer types ( Figure 5 b). Other computational studies have also identified PKMYT1 as a prognostic marker in kidney cancer cohorts [ 11 ]. Besides, we identified that hypermethylation of the CpG probe, cg02510853 leads to lower overall survival in KIRC patients ( Figure 5 a and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival analysis also showed overexpression of PKMYT1 leads to lower overall survival in ACC, BLCA, KICH, KIRC, KIRP, LGG, and LUAD cancer types ( Figure 5 b). Other computational studies have also identified PKMYT1 as a prognostic marker in kidney cancer cohorts [ 11 ]. Besides, we identified that hypermethylation of the CpG probe, cg02510853 leads to lower overall survival in KIRC patients ( Figure 5 a and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also includes the pseudokinase families, which are usually overlooked despite their links to many cancers, which can be attributed to the lack of small molecule inhibitors and assays to evaluate their mechanisms of action [ 6 , 10 ]. As of 2019, only 8% of FDA-approved small molecule inhibitors target kinases, most (70%) of which belong to the Tyr kinase family [ 11 ]. While significant kinase research has been focused on Tyr and Ser/Thr kinases, those belonging to other families have often been understudied, with very little information available on their role in cellular processes and their use as druggable targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though CAMK, CK1, or AGC kinases groups are well-known and evidenced as the primary targets for cancer, there are no investigational drugs that target these kinases are enrolled. So far only 8% of the entire kinome has been effectively “drugged” and a quarter of human kinases are vastly understudied [ 19 ]. A wide-ranging scoring system to rank and prioritize clinically relevant kinase targets of different solid tumor cancers from The Cancer Genome Atlas (TCGA) has been developed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…25 mg, 0.5 mg, 0,75 mg, and 1 mg)20 April 2010 (0.25, 0.5, and 0.75 mg) and 400 mg of pazopanib base)19 October 2009 (200 mg tablet, Prescription) (400 mg tablet has been discontinued)…”
mentioning
confidence: 99%